2020
DOI: 10.1093/ofid/ofaa439.085
|View full text |Cite
|
Sign up to set email alerts
|

40. The Role of Health Literacy in Vaccination Disparities: Do Patients Understand the Health Messages?

Abstract: Background Numerous public health campaigns are organized with the goal of improving immunization rates. However, vaccination uptake remains low among certain racial/ethnic minority groups including Hispanic patients. The level of health literacy (HL), ability to recognize the words used, may impact patients’ understanding of health-related messages and consequently health behavior and vaccination. Methods We conducted a HL s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Among those who had not vaccinated their adolescent, 60% reported that they would have their adolescent vaccinated with Tdap or MenACWY if their doctor had recommended vaccination [ 54 ]. In addition to these studies, Kricorian et al [ 55 ] conducted a health literacy survey among 43 adult females (Hispanic (n = 28) and non-Hispanic (n = 15)) attending a health fair in an underserved area of Los Angeles, California. Results showed a significantly lower percentage of Hispanic versus non-Hispanic women reporting recognition of the word “meningitis” (15% vs. 60%, p < 0.01) [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those who had not vaccinated their adolescent, 60% reported that they would have their adolescent vaccinated with Tdap or MenACWY if their doctor had recommended vaccination [ 54 ]. In addition to these studies, Kricorian et al [ 55 ] conducted a health literacy survey among 43 adult females (Hispanic (n = 28) and non-Hispanic (n = 15)) attending a health fair in an underserved area of Los Angeles, California. Results showed a significantly lower percentage of Hispanic versus non-Hispanic women reporting recognition of the word “meningitis” (15% vs. 60%, p < 0.01) [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these studies, Kricorian et al [ 55 ] conducted a health literacy survey among 43 adult females (Hispanic (n = 28) and non-Hispanic (n = 15)) attending a health fair in an underserved area of Los Angeles, California. Results showed a significantly lower percentage of Hispanic versus non-Hispanic women reporting recognition of the word “meningitis” (15% vs. 60%, p < 0.01) [ 55 ].…”
Section: Resultsmentioning
confidence: 99%